Genome-Wide Identification and Expression Profiling of ATP-Binding Cassette (ABC) Transporter Gene Family in Pineapple (Ananas comosus (L.) Merr.) Reveal the Role of AcABCG38 in Pollen Development - Chen, Piaojuan; Li, Yi; Zhao, Lihua; Hou, Zhimin; Yan, Maokai; Hu, Bingyan; Liu, Yanhui; Azam, Syed Muhammad; Zhang, Ziyan; Rahman, Zia ur; Liu, Liping; Qin, Yuan (Frontiers in Plant Science, 2017)
Pineapple (Ananas comosus L.) cultivation commonly relies on asexual reproduction which is easily impeded by many factors in agriculture production. Sexual reproduction might be a novel approach to improve the pineapple planting. However, genes controlling pineapple sexual reproduction are still remain elusive. In different organisms a conserved superfamily proteins known as ATP binding cassette (ABC) participate in various biological processes. Whereas, till today the ABC gene family has not been identified in pineapple. Here 100 ABC genes were identified in the pineapple genome and grouped into eight subfamilies (5 ABCAs, 20 ABCBs, 16 ABCCs, 2 ABCDs, one ABCEs, 5 ABCFs, 42 ABCGs and 9 ABCIs). Gene expression profiling revealed the dynamic expression pattern of ABC gene family in various tissues and different developmental stages. AcABCA5, AcABCB6, AcABCC4, AcABCC7, AcABCC9, AcABCG26, AcABCG38 and AcABCG42 exhibited preferential expression in ovule and stamen. Over-expression of AcABCG38 in the Arabidopsis double mutant abcg1-2abcg16-2 partially restored its pollen abortion defects, indicating that AcABCG38 plays important roles in pollen development. Our study on ABC gene family in pineapple provides useful information for developing sexual pineapple plantation which could be utilized to improve pineapple agricultural production.